Residual Feed Intake as a Tool for Selecting More Efficient Animals: A Review - Datt, Chander; Sharma, V. K.; Dudi, Kuldeep; Baban, Bhong Nana; Sharma, Ph. Suraj; Negesse, Tegene; Kundu, S. S.; Dutta, M. M.; Gupta, Ritika; Singh, Digvijay (Indian Journal of Animal Nutrition, 2017)
Feeds alone contributes about 60-70% of total cost of ruminant’s production. There is deficiency to the tune of 10, 37 and 35% for dry fodder, concentrates and green fodders, respectively in India. Therefore, selection of efficient animals could help in reducing the burden of already scarce feed resources. A significant improvement in profitability could be achieved through a reduction in production costs by implementation of selection strategies to improve feed efficiency. There are several measures of feed efficiency viz., feed conversion ratio, relative growth rate, partial efficiency of growth, gross efficiency and residual feed intake (RFI). RFI is difference between actual feed intake and the feed an animal is expected to consume based on its body size and growth rate. Cattle with low RFI eat less than expected for their weight and growth rate and are, therefore, more efficient than cattle with high RFI. Among the feed efficiency measures, RFI is considered to be the best as it is moderately heritable (h2=0.29-0.46) and phenotypically independent of growth rate and body weight in growing cattle and basically reflects the variation in animal’s maintenance. This makes RFI as selection tool for efficient animals. About one-third of the biological variation in RFI of these calves could be explained by differences in feed intake (2%), digestion (10%), heat increment (9%), composition of gain (5%)and activity (5%) while the remaining variation in RFI was related to differences in protein turnover, stress and tissue metabolism (37%) and differences in cellular energy expenditures such as ion pumping and mitochondrial proton leakage (27%). The low RFI animals consume less feed and produce less enteric methane. hence, there are economic and environmental benefits by selecting such efficient animals. Phenotypic selection for RFI poses challenges because it requires measurement of each individual’s feed intake for a minimum of 70 days which is expensive, time and labour intensive. As a result, there is need to develop alternative approaches like biochemical and physiological markers which could differentiate between high and low RFI animals within short period of time. Recently, genomic selection is being used as an appealing alternative tool for selection of low RFI animals. However, such studies need to be conducted using large number of animals so that more efficient animals could be selected for future breeding programmes for economic and environmental benefits.